Interviews with American Composers : Barney Childs in Conversation - Anderson, Virginia (Musicologist); Childs, Barney (Book collections on Project MUSE., 2022)
"In 1972-73, Barney Childs embarked on an ambitious attempt to survey the landscape of new American concert music. He recorded freewheeling conversations with fellow composers, most of them under forty, all of them important but most not yet famous. Though unable to publish the interviews in his lifetime, Childs had gathered invaluable dialogues with the likes of Robert Ashley, Olly Wilson, Harold Budd, Christian Wolff, and others. Virginia Anderson edits the first published collection of these conversations. She pairs each interview with a contextual essay by a contemporary expert that shows how the composer's discussion with Childs fits into his life and work. Together, the interviewees cover a broad range of ideas and concerns around topics like education, notation, developments in electronic music, changing demands on performers, and tonal music. Innovative and revealing, Interviews with American Composers is an artistic and historical snapshot of American music at an important crossroads"--